Factors Influencing Girl Students’ Drop Out in Higher Educational Institution - Subedi, Menuka (The Educator Journal, 2024)
Students’ drop out has been one of the challenges in the higher education institutions of Nepal. Compared to boys, the number of girl students’ dropout is more increasing and there might be several contributing factors. In this context, this study explores the factors influencing for the dropout of girl students in higher education in the Gorkha Campus. This study follows the theoretical tenets of Maslow’s hierarchy of needs and motivation and engagement. It is a qualitative study. The data was collected from Gorkha Campus where the total girl students of Gorkha Campus constituted the population an only 15 percent dropout students of bachelor’s degree under faculty of education and five teaching faculties of Gorkha Campus (under education stream) were selected as the respondents through random sampling procedure. Open ended interview was used as the tool for the collection of required information. This study has found that personal (student-related) factors, institution related factors, socio-cultural factors and geographical factors play highly significant role in determining girl students’ dropout. The main reasons of girl students’ dropout explored from personal or student related factors were their getting married, low academic achievement in examination, irregularity in classroom; institution-related factors were lack of academic support, feedback, motivation and encouragement from teachers, and problem of institutional information system, and alternative teaching mode; family-related factors were lack of financial support of family and different family problems and at last geographical factor were transportation problem and facility of hostel.